The securitization markets handbook : structures and dynamics of mortgage- and asset-backed securities - Stone, Charles A. [ (Charles Austin)]; Zissu, Anne (Wiley, 2012)
A comprehensive guide to the continuously evolving world of securitization The Second Edition of The Securitization Markets Handbook is a valuable resource for both experienced money managers trying to put a securitization strategy into place as well as newcomers looking to acquire a broad and strong foundation in this discipline. This edition takes a close look at the pre- and post-crash mortgage market and the mortgage-backed securities based on those mortgages, as well as other asset-backed securities including commercial paper or credit cards. The crash of the subprime market and the failure of the asset-backed markets offer an opportunity to learn about banking finance, specifically off-balance sheet finance, and the many costly mistakes that resulted in one of the most severe downturns in financial markets. With this book, you'll discover why certain mortgage and asset-backed securities imploded and others didn't. This new edition examines why the market failed and how the next crisis can be averted or made less severe. It also explains why securitization remains a primary source of capital for the mortgage market, credit card market, home equity market, auto loan market, and segments of the commercial paper market. Offers an informed overview of how the securitization market works, how to make money in it, and what's next for asset- and mortgage-backed securities after the crisis Contains new chapters on CDOs and SIVs, along with a history of the growth and crash of the subprime market, asset-backed securities, and home equity lines of credit Written by securitization experts Charles Stone and Anne Zissu Updated to reflect the current market environment, the Second Edition of The Securitization Markets Handbook offers clear, comprehensive guidance to these complex markets